COMPUTER SIMULATION OF DISPERSED MATERIALS MOTION IN ROTARY TILTING FURNACES - S. L. Rovin; L. E. Rovin; V. A. Zharanov; V. S. Mazurov (Литьë и металлургия, 2016)
The article presents the results of computer simulation of dispersed materials motion in rotary furnaces with an inclined axis of rotation. Has been received new data on the dynamic layer work that enhances understanding of heat and mass transfer processes occurring in the layer.